Performance of the Cold-Bending Channel-Angle Buckling-Restrained Brace under Cyclic Loading - Kun Wang; Junwu Xia; Xiaomiao Chen; Bo Xu; Xiangzhou Liang; Jian Wang (Advances in Civil Engineering)
In this study, three restricted cold-bending channel-angle buckling-restrained brace (CCA-BRB) specimens were experimentally characterised by a low-reversed cyclic loading test. Three specimens had steel cores with cruciform cross section. Two restraining units were assembled to form an external constraint member, each of which was composed of an equilateral cold-bending channel and two equilateral cold-bending angles via welding. A gap or a thin silica gel plate was set between the internal core and the external constraint member to form an unbonded layer. Several evaluation parameters on the seismic performance, hysteretic behaviour, and energy dissipation capability of the CCA-BRB was investigated, including hysteresis curve, skeleton curve, compression strength adjustment factor, measured and computed stiffness, energy dissipation coefficient, equivalent viscous damping ratio, ductility coefficient, and cumulative plastic deformation. The test results and evaluation indices demonstrated that the hysteretic performance of braces with a rigid connection was stable. A Ramberg–Osgood model and two model parameters were calibrated to predict, with fidelity, the skeleton curve of CCA-BRB under cyclic load. The initial elastic stiffness of the brace used in practice should contain overall portions of the brace instead of the yielding portion of the brace. Finally, all the tested CCA-BRBs exhibited a stable energy absorption performance and verified the specimens’ construction was rational.